The influence of cost benefit indicators in managing the green building - Hamzah, Mohamad Faaris (Universiti Teknologi MARA (UiTM), 2025)
A lack of practical knowledge regarding the relative influence of cost and benefit indicators hinders the development of efficient management techniques for green buildings in Malaysia. The objectives of this research are to analyse the impact of cost indicators on green building management, evaluate the influence of benefit indicators, and identify the most influential cost-benefit factors in managing green buildings. The study uses a quantitative approach, distributing questionnaire surveys to property management personnel of green buildings in Johor Bahru and analyzing the results using frequency and mean score. According to the results, cost-related indicators such as operating costs and lifespan costs have less impact than benefit-related indicators such as better indoor air quality, energy savings, and less environmental impact. These results show that property management personnel place a higher priority on the benefit indicators, especially those that concern sustainability and occupant well-being have a greater impact influence than cost indicators such as energy and water saving.